Influence of social media characteristics on consumers' purchase intention - Kajanthy, S.; Sathana, V. (University of Jaffna, 2015)
In 21 century, Social Media has become the modern tool for people to engage socially. Building on the foundation of Web 2.0, Social Media applications have facilitated extraordinary growth in human interaction in modern times. Social Media is being considered playing an important role in customer buying decisions, however little studies have explored its impact over the Customer Purchase Intention. Even though Social Media have been recognized as potentially the most powerful medium for relationship building, there is a lack of understanding in terms of how and why firms are actually using them. The objective of the study was to look at the influence of Sri Lankan Consumers' Purchase Intention through Social Media. This study was conducted by using quantitative research methodology. In order to collect the data necessary to measure the constructs related to the subjects of the study, the researcher selected 155 Sri Lankan customers who are actively participating in any Social Media Platforms. Data analysis was conducted with the path analysis by using the Structural Equation Model approach. The results of the present study is supported by the mediating role of perceived risk, trust and perceived value in relationship between Social Media and Consumers' Purchase Intention. This study indicated that, there is a positive association has been found between Social Media and Consumers' Purchase Intention (b=0.711; p=0.000) before the mediation. And after the mediation, due to the mediating effect of perception factors the beta value has reduced (b= .478; p=0.000). These finding indicate to marketing managers that Social Media has become an important marketing tool to reach consumers. It also indicates that cyber world play an important role in modern marketing, enabling marketers to reach customers faster and more efficiently.
Keywords: Perception Factors; Purchase Intention; Social Media